AI in U.S.-China Rivalry: Scenarios and Policies for Small States - Alexis Colmenarez (Foresight and STI Governance, 2025)
Emerging disruptive technologies such as artificial intelligence (AI) are fueling global rivalry by changing the power dynamics among countries. This article examines the implications of AI for the prospects of defense competition between major powers such as the United States and China. It presents possible scenarios of such competition through 2050 and their implications for smaller countries with limited geopolitical influence as they adapt to the increasingly complex context these processes create. The scenarios provide not only structured pictures of possible futures but also a strategic canvas for developing proactive national security policies in the changing international landscape. In the context of rapid technological advances and strategic competition, smaller countries face both challenges and opportunities as they navigate their own paths. The proposed recommendations aim to “level the playing field” and help such states not only address the challenges posed by AI in the military sphere but also seize the opportunities arising from technological shifts. The findings presented can serve as a basis for developing national security strategies even in the context of institutional and infrastructural limitations. Decision makers will be able to navigate and effectively act in a complex, changing arena, the dynamism of which is largely determined by AI technologies.